The Impact of Instant Noodle Consumption Patterns on Hemoglobin Levels among Medical Laboratory Technology Students at Poltekkes Medan - Evi Irianti; Ice Ratnalela Siregar; Elizawarda Elizawarda; Rinson Sitohang (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Instant noodles are widely consumed worldwide due to their convenience, affordability, and long shelf life, particularly among university students. Despite their popularity, these products are nutritionally imbalanced, with high in carbohydrates and sodium, but low in protein, iron, and essential vitamins, raising concerns about their impact on hemoglobin levels and anemia risk. This study specifically examines hemoglobin status in relation to both frequency and duration of instant noodle consumption, while considering gender and sleep duration. A cross-sectional analytical study was conducted among 163 third-year Medical Laboratory Technology students at Poltekkes Kemenkes Medan. Hemoglobin concentration was measured from venous blood samples, while dietary patterns, sleep duration, and instant noodle consumption habits were assessed via structured questionnaires. Associations were analyzed using the Chi-square test (p < 0.05). Most students maintained normal hemoglobin levels regardless of instant noodle consumption frequency or duration. Female students had lower hemoglobin than males, reflecting hormonal and menstrual influences. Sleep duration did not significantly affect hemoglobin. Nearly all students reported adding vegetables and eggs to their noodles, potentially mitigating the adverse effects of sodium and supporting iron absorption. However, this effect was not statistically controlled, rendering the observed maintenance of hemoglobin suggestive rather than definitive. Hemoglobin status in young adults is primarily influenced by gender-related biological factors and overall dietary quality, rather than instant noodle consumption patterns alone. The findings highlight the importance of nutrient-rich complementary foods and warrant longitudinal studies to clarify the causal impact of dietary habits on hematological health Keywords: Noodles, Hemoglobins, Anemia, Sleep, Gender Factors